Implementasi Kebijakan Larangan Parkir Liar di Kota Surabaya (Studi Kasus Parkir Pasar Kapasan) - Firly Erysa Faldilal Nuraini; Gina Nur Maya Jannah; Safna Humayrah Karfen; Aurel Devany Salsabila; Muhammad Agus Muljanto (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
The Kapasan Market area is one of the areas in the city of Surabaya where parking problems often occur. Some illegal parking attendants often park visitors' vehicles on the side of the road because of limited parking spaces and supervision, causing traffic jams around Kapasan Market which the public often complains about. The Surabaya City Transportation Department (Dishub) is guided by Surabaya City Regional Regulation Number 3 of 2018 concerning the Implementation of Parking in the City of Surabaya in implementing the parking ban policy in the City of Surabaya, including in the Kapasan Market area. This research aims to find out whether the parking ban policy has been implemented well and is appropriate, especially in the Kapasan Market area. This research uses a qualitative approach with descriptive methods. The research uses primary data obtained through direct observation of research objects, interviews, and documentation as well as secondary data from documents, books, the internet, and other written sources. Determining informants for interview activities using purposive sampling techniques to the Head of the Public Roadside Parking Division. The research results show that the implementation of the policy of prohibiting illegal parking in the city of Surabaya, especially at Kapasan Market, is quite good. four of the six policy implementation indicators according to Van Meter and Van Horn have been met so that the public can feel the response from the government regarding illegal parking that they complain about.